PHYSICAL EDUCATION, BODY AND MENTAL HEALTH: AN EXPERIENCE IN A PSYCHOSOCIAL CARE CENTER (CAPS) (Fiep Bulletin - online, 2011)
This study is characterized as an essay that deals with Physical Education and Health Metal, in the case of the intervention on the body and health of users of a CAPS (community mental health services). The study was conducted with empirical support for a curricular done in a Bachelor's Degree in Physical Education during the first half of 2009. The methodology followed the principles of ethnography, conceived as Loïc Wacquant (2002).The conclusion shows that physical education can have a role to users of CAPS, helping them to build a position of autonomy and not as subjection to your health and your body.
Keywords: Physical Education; Body; Mental Health